2019
DOI: 10.1590/1413-81232018247.17272017
|View full text |Cite
|
Sign up to set email alerts
|

Ganho de peso por década entre trabalhadores de um hospital público: estudo de coorte histórica

Abstract: Resumo O objetivo do estudo foi avaliar as modificações no perfil nutricional dos trabalhadores de um hospital público por três décadas e sua associação com fatores ocupacionais. Estudo de coorte histórica com trabalhadores ativos em 2013 admitidos em três períodos. Foram coletados dados sociodemográficos, de peso e de estatura, e calculado o índice de massa corporal (IMC) do exame admissional e de dois exames periódicos/década. Avaliados 386 trabalhadores (76,4% mulheres, 88,1% de cor de pele branca e 29,3±7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
5
Order By: Relevance
“…However, these findings are still controversial, as in the studies of Boyce et al 30 with call center employees, and Scherr et al 26 , with health care and pharmaceutical industry workers, in which the findings showed a positive association between weight gain and increasing age. In the study of Montzel et al 31 , the authors found no significant difference between age and nutritional status in the analysis over three decades of workers at a tertiary care public hospital of Porto Alegre, Brazil.…”
Section: Discussionmentioning
confidence: 93%
“…However, these findings are still controversial, as in the studies of Boyce et al 30 with call center employees, and Scherr et al 26 , with health care and pharmaceutical industry workers, in which the findings showed a positive association between weight gain and increasing age. In the study of Montzel et al 31 , the authors found no significant difference between age and nutritional status in the analysis over three decades of workers at a tertiary care public hospital of Porto Alegre, Brazil.…”
Section: Discussionmentioning
confidence: 93%
“…A média da percepção de qualidade de vida dos hipertensos foi menor (30,9; desvio padrão -DP: ±3,50) do que a dos não hipertensos (31,2; DP: ±3,51), porém, sem significância estatística (valor de p = 0,14).…”
Section: Resultsunclassified
“…Neste estudo, não foi observada associação significativa entre turno de trabalho e hipertensão arterial, possivelmente devido à baixa frequência de trabalho noturno na amostra estudada. Resultado semelhante foi observado em uma coorte realizada no Brasil com trabalhadores de um hospital público 9 . Em contrapartida, em uma coorte de trabalhadores homens, na Espanha, foi observado que a incidência de doenças crônicas ocorreu mais nos que assumiam turnos noturnos de trabalho e isso pode contribuir para a maior prevalência de doenças crônicas devido aos ritmos circadianos alterados, estresse e alterações bioquímicas que ocorrem no organismo 12 .…”
Section: Discussionunclassified
See 2 more Smart Citations